2017
DOI: 10.1080/10402004.2017.1333664
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Thermoscopy Characterization of Water Contaminated Grease

Abstract: Measuring water content in hydrocarbons can be done a number of different ways, but few of them apply well to grease samples. This month's Editor's Choice paper investigates the use of three different dielectric cells (parallel plate, coaxial and interdigitated fringe) to estimate water content in greases. The results are very promising using calcium sulfonate complex greases, with further work required to determine suitability with different thickener technologies that are less hydrophilic, and different addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Low frequencies have an advantage of having an e ' value of orders of magnitude higher than the typical higher frequencies used in dielectric measurements, in addition to the temperature dependence used in this dielectric thermoscopy method. A brief background was further described in a previous paper (7). As a further observation in Fig.…”
Section: Greasementioning
confidence: 94%
See 3 more Smart Citations
“…Low frequencies have an advantage of having an e ' value of orders of magnitude higher than the typical higher frequencies used in dielectric measurements, in addition to the temperature dependence used in this dielectric thermoscopy method. A brief background was further described in a previous paper (7). As a further observation in Fig.…”
Section: Greasementioning
confidence: 94%
“…The theoretical performance of the sensor is given next. A similar derivation is given in (7); however, the theory has since then been further modified in this article to accommodate estimating the difference due to a thin coating with a different dielectric constant in between the traces and on top. This could be useful if it is found that coatings of a different hydrophobicity help improve the performance or behavior of the sensor with different greases.…”
Section: Sensor Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they use hazardous chemical reagents and fragile glass vessels. Beyond conventional grease-water content determination methods, there are also some novel approaches that have not yet been widely exploited, such as dielectric thermoscopy (Dittes et al, 2018). This method applies the temperature dependence of the dielectric properties of water-contaminated grease inside a test cell to estimate its water content by quantifying the change in the dielectric constant over a temperature change within a certain frequency range.…”
Section: Introductionmentioning
confidence: 99%